What does it mean to follow? A critique of the followership literature and a conceptual model of the emergence of downward following - Bastardoz, Nicolas; Adriaensen, Sofie (Frontiers in Psychology, 2023)
What does it mean to follow? In this paper, we systematically review the followership literature for the period 2017–2021. Our review shows that the followership literature suffers from three major issues that limit its validity. The followership field is dominated by a role-based approach equating direct reports with followers; empirical studies fail to study actual following behaviors, and there are no studies of downward following, which we define as any behavior or effort aimed at achieving a shared goal, carried out by an individual in a position of formal power who is influenced by one or more individuals in a position of inferior authority. Our manuscript builds on the process approach to study what it means to follow. We argue that the followership field needs to study actual followership behaviors at the micro “interaction episodes” and rely on quantitative behavioral coding. We then propose a conceptual, multi-level model that details antecedents and boundary conditions of the emergence of downward following. We conclude by discussing the organizational implications of our approach and model.